Synthesis of highly transparent and thermally stable copolyimide with fluorine‐containing dianhydride and alicyclic dianhydride. Issue 17 (22nd October 2019) - Xu, Wenhua; Ma, Xiaoru; Su, Yuanhai; Song, Yang; Shang, Minjing; Lu, Xuemin; Lu, Qinghua
ABSTRACT: The development of optical films is highly desirable for applications in flexible displayers. In this work, a copolyimide (co‐PI) film with high thermal stability and high transparency was prepared by the copolymerization of 2, 2′‐bis(trifluoromethyl)‐4, 4′‐diaminodiphenyl ether, cyclobutanetetracarboxylic dianhydride, and 4, 4′‐(hexafluoroisopropylidene)diphthalic anhydride (6FDA). The effects of aliphatic dianhydride and fluorine dianhydride monomers on the optical, thermal, and mechanical properties of the co‐PIs were discussed in detail based on the experimental results and theoretical simulations. We found that the preparation of polyimide (PI) based on the combination of two dianhydrides could obtain the PI film with excellent comprehensive performance due to nonconjugated structure and strong electron‐withdrawing effect. Through the structure and composition optimization, a PI film of PI‐6FDA‐70 with T g of 300 °C, T d 10% more than 500 °C, the average transparency of 90% and the elongation at the breakage more than 8% was prepared. Such molecular design provides a practical approach to develop high‐performance colorless PI films. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48603. Abstract : Schematic diagram of the procedure for preparing PAA and co‐PI films.